Digital Coaching And The Use Of Technology In The Coaching Profession: A Systematic Literature Review - Syahrul Zaum (Journal of Sport Education, Coaching, and Health (JOCCA), 2025)
The rapid development of digital technology has significantly transformed the sports coaching profession, shifting traditional coaching practices toward data-driven and technology-enhanced approaches. Digital coaching integrates various technological tools, including wearable devices, artificial intelligence (AI), mobile applications, video analysis systems, and athlete management platforms, to improve coaching effectiveness and athlete performance. This study aimed to systematically review the development, implementation, benefits, and challenges of digital coaching and technology utilization within the coaching profession. This study employed a Systematic Literature Review (SLR) following the PRISMA 2020 guidelines. Articles were retrieved from Scopus, Web of Science, ScienceDirect, PubMed, Google Scholar, and SINTA-indexed journals published between 2015 and 2025. From an initial 312 records identified, 30 eligible studies met the inclusion criteria and were included in the final synthesis. Data were analyzed using thematic synthesis to identify major trends and patterns. The findings revealed that wearable technology and GPS tracking systems were the most frequently utilized technologies (26.7%), followed by video analysis software (20.0%), mobile coaching applications (16.7%), artificial intelligence systems (13.3%), athlete management platforms (13.3%), and virtual reality technologies (10.0%). Digital technology positively influenced performance monitoring (83.3%), coaching decision-making (73.3%), coach–athlete communication (66.7%), individualized training programs (63.3%), and injury prevention (60.0%). However, barriers such as limited digital competence (80.0%), high implementation costs (70.0%), and data privacy concerns (56.7%) were also identified. In conclusion, digital coaching has become a strategic component of modern coaching practice, enhancing evidence-based decision-making and athlete development while requiring continuous professional development and effective technological integration.